Serum uromodulin is associated with impaired glucose metabolism. Issue 5 (February 2017) - Leiherer, Andreas; Muendlein, Axel; Saely, Christoph H.; Kinz, Elena; Brandtner, Eva M.; Fraunberger, Peter; Drexel, Heinz
Abstract : Abstract: Uromodulin is the most abundant urine protein under physiological conditions. It has recently been described as a serum and plasma marker for kidney disease. Whether uromodulin is associated with impaired glucose metabolism is unknown. We therefore measured serum uromodulin and glucose traits in a cohort of 529 consecutively recruited patients. Serum uromodulin was significantly and inversely correlated with fasting plasma glucose ( r  = −0.161; P  < 0.001), with plasma glucose 2 hours after an oral 75 g glucose challenge ( r  = −0.158; P  = 0.001), and with HbA1c ( r  = −0.103; P  = 0.018). A total of 146 (27.6%) of our patients had type 2 diabetes mellitus (T2DM). Analysis of covariance confirmed that T2DM was an independent determinant of serum uromodulin (F = 5.5, P  = 0.020) after multivariate adjustment including hypertension and glomerular filtration rate. Prospectively, uromodulin was lowest in patients with T2DM at baseline, higher in initially nondiabetic subjects who developed diabetes during follow-up (FU) and highest among nondiabetic patients (147.7 ± 69.9 vs 164 ± 67 vs 179.9 ± 82.2 ng/mL, P trend < 0.001). Similar results were seen with respect to prediabetes (168.0 ± 81.2 vs 172.8 ± 66.3 vs 188.2 ± 74.0 ng/mL, P  = 0.011). We conclude that serum uromodulin is significantly associated with impaired glucose metabolism and the development of prediabetes and diabetes.